Viscous Fingering of Irreducible Water During Favorable Viscosity Two-Phase Displacements. (July 2021) - Mejia, Lucas; Mejia, Miguel; Xie, Chiyu; Du, Yujing; Sultan, Abdullah; Mohanty, Kishore K.; Balhoff, Matthew T.
Abstract: Multiphase displacements in porous media are expected to be stable if the injectant has a smaller mobility than the resident phase and injection velocity is small. We investigate two-phase displacements (aqueous phase displacing oleic phase) at favorable mobility ratios, which are expected to be stable, and find that the presence of low-viscosity irreducible water promotes the formation of viscous instabilities. Microfluidic experiments and Lattice Boltzmann (LB) simulations were utilized to identify the effects of pore-scale mobilization of irreducible water on centimeter-scale flow patterns during favorable displacements. Displacements in glass micromodels showed the presence of low viscosity irreducible water resulted in fingering and early breakthrough compared to experiments with high viscosity irreducible water (glycerol solution). The LB simulations were used to explain that fingers formed because irreducible water was mobilized ahead of the injected water. The low viscosity aqueous front fingered through the oil as the viscosity of the oil was larger than that of the low viscosity aqueous phase bank. Additionally, we conducted a coreflood that showed breakthrough of the aqueous phase occurred slightly earlier when irreducible aqueous phase viscosity was low (1 cp) than when irreducible aqueous phase viscosity was large (69 cp). The novelty of this work lies in showing that presence of low viscosity irreducible water may result in an unstable displacement of medium viscosity oil by high viscosity aqueous solution at small flooding velocities.